Analysis of Students' Difficulties in Understanding Concepts and Solving Fraction Problems in Class V of State Elementary School 5 Palangka - Murjani, Didy; Kartini, Nurul Hikmah; Elhawwa, Tazkiyatunnafs (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: This research is based on researchers' observations of class V students at State Elementary School 5 Palangka. The phenomena found were not being able to differentiate the technical names between the numerator and the denominator, not being able to equate the denominators in the arithmetic operations of addition and subtraction, the inability to remember to cross-multiply the numerator and denominator in multiplying fractions and forgetting the concept of division in fractions and when Solving word problems students have difficulty understanding the questions because they cannot change the questions into fraction form. Aim: The aim of this research is to find out the causes of difficulties experienced by class V students at State Elementary School 5 Palangka in understanding the concept of fractions and what difficulties experienced by class V students at State Elementary School 5 Palangka in solving fraction problems. Method: This research is a qualitative descriptive study, The method used to carry out research uses descriptive methods. Results and Dıscussion: Based on the results of trials carried out by researchers on class V students at State Elementary School 5 Palangka, it can be seen that there were several class V students who got scores below the average of the Minimum Completeness Criteria scores. These students are students who have difficulty understanding and solving fraction material problems. The difficulties experienced by students in class V State Elementary School 5 Palangka are difficulty in simplifying fractions, not being able to equate unequal denominators and same denominators in the arithmetic operations of adding and subtracting fractions, and when solving word problems students have difficulty understanding the questions because they don't You can change the question into fraction form. Conclusion: Based on the results and discussion of the research, it can be concluded that the difficulties of students in understanding the concept and solving fraction problems in class V were found to be 3 difficulties, namely difficulty in simplifying fractions, not being able to equate unequal and same denominators in the arithmetic operations of adding and subtracting fractions, and When solving word problems, students have difficulty understanding the questions because they cannot change the questions into fraction form.